(untitled) (Khartoum Journal of Pharmaceutical Sciences, 2021)
The treatment of cancer with most anticancer drugs is complicated by the risk of numerous severe toxicities,many of which are life-threatening.The toxicities related to anticancer therapies are the most important factors restricting the use of potentially curative doses.This study aimed to assess the most common chemotherapy side effects developed and their treatment in the Khartoum oncology hospital emergency ward. This study was conducted at the Khartoum oncology hospital’s emergency ward from March to May 2019.The data were collected from the medical records and individual interviews with the patients using a structured data collection sheet. Total of 100 patients were involved in this study, the most common side effects were nausea and vomiting (40%), abdominal pain (29%) of patients, diarrhea (19%), hypotension, fever, body pain, each experienced by (10%) of patients. Febrile neutropenia and dehydration, experienced by (9%) each. Moreover, the most common management of side effects was IV hydration used among 87% of patients, acid suppressants, and antiemetics used among 45% and 39% of patients,respectively.Antibiotics were used for 30% of patients; corticosteroids were used among 29% of patients.Antispasmodic were used among 27%, and analgesia used for 26 %.The association between the number of chemotherapeutic agents and side effects was signifcant (P=0.023).The study revealed that the most common side effects of chemotherapy were nausea and vomiting, abdominal pain, and diarrhea.The management mainly by intravenous hydration, antiemetic, acid suppressants, and antibiotics.